Reconstructing the Lost Beginning of Suetonius' Divus Iulius*. (25th November 2015) - Garrett, Phoebe
Abstract: It appears that the beginning of Suetonius' Divus Iulius is now lost. C.L. Roth, in 1865, argued that the work was acephalous by setting out the four things that were missing from the Divus Iulius: first, the title of the work; second, the dedication to Septicius Clarus, which is known to us only from John Lydus' sixth-century work De Magistratibus 2.6.4; third, the family tree of the Caesars; fourth, the beginning of the Divus Iulius with the details about its Trojan and Alban origins, the origin and name of the Caesars, the omens of future greatness, his education, and his first offices. These were, as Roth saw it, all things Suetonius was in the habit of giving in the extant Lives. 1 These things are indeed absent from the text as we have it. It remains to test whether those things are all really standard inclusions in a Suetonian introduction. This paper approaches the lost beginning of the Divus Iulius by comparing the constructions of Suetonius' extant openings, in particular the family trees, with Philemon Holland's reconstruction of 1606. The comparative study will consider how the lost part of the Divus Iulius might reflect what Suetonius includes in other beginnings, and how it might have differed from those others. The study will also set out the elements that Suetonius appears to have considered essential to an introduction, thereby bringing into focus the places where the interests of renaissance authors differed from his own.